Enhanced sensing performance of carboxyl graphene–ionic liquid attached ionic polymer–metal nanocomposite based polymer strain sensors. Issue 31 (19th July 2018) - Panwar, Varij; Anoop, Gopinathan
Abstract : Here, we show that biocompatible IPMNC sensors based on a carboxyl graphene–acidic ionic liquid–polyvinylpyrrolidone–polystyrene sulfonic acid ionic blend membrane can generate a high sensing current (6 mA cm −2 ) with a bending strain of 0.009. Abstract : Soft bendable polymer sensors have been widely used to monitor prosthetics, heartbeat, joint pain, and several other medical conditions because of their flexible nature. Recently, sensors based on piezoelectric inorganic materials, conducting polymers, and commercial Nafion based ionic polymer–metal nanocomposites (IPMNCs), have been extensively studied for sensor applications; however, existing inorganic and polymer materials exhibit low sensing currents due to weak interfacial bonding between the electrode and sensing material. Here, we show that biocompatible IPMNC sensors based on a carboxyl graphene (COG)–acidic ionic liquid (IL) (1-butyl-3-methylimidazolium-hydrogen sulfate)–poly(vinylidene fluoride–trifluoroethylene–chlorotrifluoroethylene) [P(VDF–TrFE–CTFE)]–polyvinylpyrrolidone (PVP)–polystyrene sulfonic acid (PSSA) ionic blend membrane can generate a high sensing current (6 mA cm −2 ) with a bending strain of 0.009. The ionic exchange capacity (IEC) (1.36 times), proton conductivity (3.4 times), and Young's modulus (176 times) of P(VDF–TrFE–CTFE)/PVP/PSSA/COG ionic blend membranes are enhanced compared to those of P(VDF–TrFE–CTFE)/PVP/PSSA. In comparison to a commercial Nafion membrane, enhanced values of water uptake (WUP) (5.61 times), IEC (3.26 times), and Young's modulus (6 times) were achieved by our P(VDF–TrFE–CTFE)/PVP/PSSA/COG/IL ionic blend membrane. Polymer sensors based on (PVDF–TrFE–CTFE)/PVP/PSSA/COG/IL IPMNC exhibit stable sensing currents in dry conditions for up to 6000 cycles. Our proposed blend fabricated through attaching COG and IL will find applications in several other devices such as supercapacitors due to its high capacitance (3.92 mF).